2018
DOI: 10.1007/s12687-018-0375-3
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of patients seeking to participate in variant of uncertain significance reclassification research

Abstract: Patients' understanding of a genetic variant of unknown clinical significance (VUS) is likely to influence beliefs about risk implications, consequent medical decisions, and other actions such as involvement in research. We interviewed 26 self-selected participants with a clinically identified VUS before they enrolled into a VUS reclassification study. Semi-structured interviews addressed topics including motivation to get genetic test, experience with the VUS result, affective responses to receiving VUS, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 32 publications
5
27
0
Order By: Relevance
“…The recommended practice of periodically checking back for VUS reclassification was used by some patients and seemed to be beneficial for uncertainty management. This finding is similar to that of a prior study which found that information seeking about VUS was not associated with patient behavior in response to VUS (Makhnoon, Garrett, et al, ; Makhnoon, Shirts, et al, ). Most patients did not attempt to read the genetic test report that they were given because they trusted their providers to read and interpret the report for them.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The recommended practice of periodically checking back for VUS reclassification was used by some patients and seemed to be beneficial for uncertainty management. This finding is similar to that of a prior study which found that information seeking about VUS was not associated with patient behavior in response to VUS (Makhnoon, Garrett, et al, ; Makhnoon, Shirts, et al, ). Most patients did not attempt to read the genetic test report that they were given because they trusted their providers to read and interpret the report for them.…”
Section: Discussionsupporting
confidence: 90%
“…However, discordant provider explanations of the implication of this epistemic uncertainty for patients' diagnosis, prognosis, and therapy was an important contributor to the overall scientific issue of uncertainty. These findings are supported by results from a several other studies which also observed variation in practices of reporting, disclosure, and clinical management of patients with VUS (Makhnoon, Garrett, et al, 2018;Murray et al, 2011;Solomon et al, 2017 findings, we offer a provisional framework for VUS-related uncertainty management strategy that may offer clinically actionable approaches to manage VUS (Figure 2).…”
Section: Discussionsupporting
confidence: 82%
“…Lower problems in women receiving a VUS result compared with non-carriers suggests a particular attention to the content of counselling in the case of this particular genetic test result. A VUS result raises uncertainty about clinical management 22. In these study settings, the message conveyed by the communication of a VUS seemed more reassuring than that of an uninformative negative test result.…”
Section: Discussionmentioning
confidence: 88%
“…Prolonged clinical distress is uncommon after single-gene testing for HBOC susceptibility 19. However, an inconclusive result such as a VUS may elicit misunderstanding,20 21 uncertainty21 22 and decisional conflicts about clinical management,23 potentially leading to increased distress,24 miscommunication between family members25 and inadequate cancer risk management decisions 21 26 27. On receiving a pathogenic moderate-penetrance gene variant, counselees may experience higher distress and uncertainty compared with a negative, VUS and even a pathogenic high-penetrance variant 28…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we found that actively involving patients as collaborators in charge of family communication for their own VUS reclassification studies led to reclassification of approximately 60% of variants, with an average time to classification of <1 year (Makhnoon, Garrett, Burke, Bowen, & Shirts, ; Tsai et al, , ). Unique aspects of this process included conveying uncertainty related to the clinical significance of the variant, patients’ and relatives’ involvement in aspects that might be considered research activities, and communication with relatives extending beyond the first and second degree of relationship.…”
Section: Introductionmentioning
confidence: 99%